The Influence of Service Quality On Customer Loyalty and Satisfaction as an Intervening Variable in using Bus Transportation Services - Kurniati, Kurniati; Basalamah, Ridwan; Asiyah, Siti (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research Objectives: The aim of this research is to determine the quality of service that directly influences loyalty to using bus transportation services. To find out whether the quality of service has a direct effect on consumer satisfaction when using bus transportation services. To find out customer satisfaction has a direct effect on loyalty in using bus transportation services. To find out the indirect effect of service quality on loyalty through customer satisfaction as an intervening variable in using bus transportation services. Design/Method/Approach: This research uses explanatory research, this research was conducted on bus customers. Research Findings: The results of this research show that Service Quality directly has a positive and significant effect on Consumer Satisfaction in using Bus transportation services. Service Quality directly has a positive and significant effect on Loyalty in using Bus transportation services. Consumer satisfaction has a positive and significant direct effect on loyalty in using bus transportation services. Service quality indirectly influences loyalty with customer satisfaction as an intervening variable in using bus transportation services. Theoretical Contribution/ Originality: This research integrates service quality, consumer satisfaction, and loyalty in the context of bus transportation and provides a holistic view of the relationship between the three. Practical Implications: The results of this research can help bus companies improve service and customer satisfaction to strengthen loyalty Research Limitations: This research focuses on one industry, so the generality of the findings is limited to the bus transportation context. Further research is needed to dig deeper into other factors that might influence customer loyalty.